Formation, morphology and function of a 3D hepatocyte-hepatic stellate cell co-culture system - Thomas, Robert James (2006)
In these studies the ability of a three-dimensional hepatocyte-stellate cell co-culture system to preserve some key aspects of differentiated hepatocyte function in vitro is demonstrated. A poly(DL-lactic Acid) surface allows dynamic and rapid interaction of hepatocytes and stellate cells to form co-culture spheroids in a complex multistage process (shown by time lapse microscopy). After five days the spheroids have developed a substantial extracellular matrix support and hepatic ultra-structure including bile canaliculi, tight junctions, desmosomes and lipid storage. The distribution of the stellate cells in the final structure is related to their motile and aggregating role in spheroid formation, i.e. mainly central and peripheral, and provides a unique and generically applicable insight into the dynamics of multicellular spheroid formation where aggregation is induced by one cell type and imposed on another.